Language and business: Patterns in the annual report translations of public companies in Indonesia - Emma Natasha Octoveria; Aris Munandar (Studies in English Language and Education)
The economic benefits of English proficiency and the pervasive use of English in business communications have increased the demand to translate business texts. As a part of the business text genre, an annual report is translated into English as a form of information disclosure for foreign investors of a public company in Indonesia. This study aims to explore translation patterns in annual reports from Indonesian to English using Catford’s classification of translation shifts and Becher’s classification of explicitations and implicitations. This research employed a mixed-method approach with both qualitative and quantitative analyses. The data sources were six annual reports of Indonesian public companies in three sectors (financial, non-cyclical consumer, and energy) obtained from each company’s official website. By applying qualitative and quantitative approaches, the analyses reveal patterns of annual report translation. The findings of this study indicate that there were significant differences between annual reports in various sectors, as evidenced by the chi-square test result (X2(4, N = 138) = 20.21, p .001) and by variations in how translation shifts are used. Patterns in translating annual reports from Indonesian to English were identified, namely the use of explicitations and implicitations in interactional, cohesive, and denotational manners through translation shifts. The results of this study suggest that annual report translation was made possible through shifts involving changes in syntactic structure and the choice of information to be added, omitted, or substituted.